2021
DOI: 10.3390/ijerph18147512
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in Exposure to Ambient Air Neurotoxicants and Disparities in Markers of Neurodevelopment in Children by Maternal Nativity Status

Abstract: Exposure levels to environmental pollutants vary significantly among different populations. These inequities in exposure to hazardous air pollutants (HAP) among different populations can contribute to disparities in neurodevelopmental outcomes. The aim of this study was to determine if exposure to HAP varies by maternal nativity status, a demographic marker often overlooked in the study of health disparities. We also assessed if those inequalities in exposure levels are associated with neurodevelopmental measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 63 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…We identified 17 total studies that analyzed immigrant disparities in exposure to or health effects from air pollution. 57 73 Of the 17 studies, 12 were based in the United States and 5 in Canada. These studies often found that immigrants or areas with higher immigrant proportions had higher exposures to air pollution compared with nonimmigrants or areas with lower immigrant proportions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We identified 17 total studies that analyzed immigrant disparities in exposure to or health effects from air pollution. 57 73 Of the 17 studies, 12 were based in the United States and 5 in Canada. These studies often found that immigrants or areas with higher immigrant proportions had higher exposures to air pollution compared with nonimmigrants or areas with lower immigrant proportions.…”
Section: Resultsmentioning
confidence: 99%
“…In the United States, there was a range of small area-level studies and large regional studies with individual data that found disparities in exposures to monitored black carbon (BC) 72 and ozone ( ), 68 as well as model-predicted fine particulate matter ( ) 61 , 63 , 65 , 73 and hazardous air pollutants (HAPs). 57 , 66 , 67 , 69 HAPs are 187 toxic air chemicals, including benzene, perchloroethylene, and methylene chloride, on a list maintained through the U.S. Environmental Protection Agency’s (EPA) 2011 National Air Toxics Assessment. 74 In California, an area-level study found that communities with high immigrant Vietnamese populations had higher BC levels compared with the statewide mean BC concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations